Validation of a tool for assessing the quality of pharmaceutical services - Marly Aparecida E. Cosendey (Cadernos de Saúde Pública)
This paper presents the validation process for a tool assessing basic pharmaceutical services through an analysis of the implementation of a Basic Pharmaceuticals Distribution Program by the Brazilian Federal government. The process began with the drafting of a theoretical model, based on a state-of-the-art review and allowing the selection of various conceptual dimensions and respective criteria that best represented the construct. The second step involved weighting indicators for the construction of quality scores. Three models were tested for ranking implementation levels, and seven simulations were conducted, determining the score most closely reflecting the selected indicators in two different matrices. The objective was to select the most coherent and consistent version between implementation levels and expected outcomes, while simultaneously enhancing validity of chosen criteria. Testing of the various models and the results obtained showed that augmenting the validity of the study was possible without altering data. This endeavor is justified in understanding the scope and limitations of these measurements and of the choices involved in issues concerning their weighting and interpretation.